Memahami Pendidikan Islam - Subhan, Fauti (Nadwa: Jurnal Pendidikan Islam, 2013)
This article discusses the relationship between Islamic education and various elements of life. The linkage between the theoretical side of Islamic education and the practical side of Islamic education is also presented here. In the study, the theoretical and applied dimensions of Islamic education can be discussed separately, but in practice, these two dimensions are inseparable. In principle, the Islamic education issues cannot be separated from any variety of issues. The Islamic education is always associated with the various elements of life, es-pecially human beings. Human beings can grow and develop properly with Is-lamic education. Conversely, humans (Muslim) also become actors for the de-velopment and the decline of Islamic education. The relationship between Mus-lims and Islamic education just likes a piece of money, which is composed of two different sides, but inseparable one another. In Islamic societies, education be-comes a key of progress.AbstrakTulisan ini membahas tentang keterkaitan antara pendidikan Islam dengan berbagai elemen kehidupan. Keterkaitan antara sisi teoritis pendidikan Islam de-ngan sisi praktis pendidikan Islam juga disampaikan di sini. Secara kajian, di-mensi teoritis dengan aplikatif pendidikan Islam dapat dibahas sendiri-sendiri, tetapi secara praktis, kedua dimensi tersebut tidak bisa lepas satu sama lain. Pada prinsipnya, persoalan pendidikan Islam tidak dapat dilepaskan dari beragam per-soalan lainnya. Pendidikan Islam selalu terkait dengan berbagai elemen kehi-dupan, terutama manusia. Melalui pendidikan Islam manusia dapat tumbuh dan berkembang dengan baik. Sebaliknya, manusia (Muslim) juga menjadi aktor dari maju atau mundurnya pendidikan Islam. Antara umat Islam dan pendidikan Is-lam merupakan dua hal yang dapat diibaratkan seperti sekeping uang, yakni terdiri dari dua sisi yang berbeda tetapi tidak terpisah antara satu dengan lainnya.Â